THE EXPERIENCE AND FEATURES OF CLINICAL EDUCATION AT ’PROGRESS’ UNIVERSITY - Muradyan, Lilit; Stamboltsyan, Anahit (Bulletin of Yerevan University C: Jurisprudence, 2026)
The article is dedicated to the educational experience and distinctive features of the legal clinic at "Progress" University in Armenia. It explores the clinic’s role as an educational and social institution, its functions, working methods, and contribution to students’ practical preparedness. Special attention is given to the clinic’s educational and social functions, as well as its role in the professional development of future lawyers.